Electronic structure of topological quantum materials probed by angle-resolved photoelectron spectroscopy - Schröter, N (2017)
This thesis investigates the electronic structure of four separate topological quantum material systems by angle-resolved photoelectron spectroscopy (ARPES): 1. LaBi is a semimetal with an extremely large magnetoresistance (XMR) that remains unsaturated even at large magnetic fields. Our ARPES measurements of LaBi indicate the existence of a strong topological phase that may be unique within the family of lanthanum monopnictides. Additionally, our characterization of its bulk electronic structure finds a large imbalance between the electron and hole carrier densities, which challenges the previously assumed scenario of perfect carrier compensation as the origin of the XMR. 2. Three dimensional topological insulators (TIs) can be divided into two classes: strong TIs that host TSSs on all surfaces, and weak TIs, which host TSSs only on some surfaces, which are expected to harbour novel physical phenomena. Yet, despite multiple theoretical proposals and experimental reports, "smoking-gun" evidence for the existence of a weak topological phase is still elusive. Here, by performing ARPES measurements for the surface states of two distinct crystal surfaces, we can conclusively confirm the existence of a weak topological phase in the semimetal TaSb2, which may be related to its negative longitudinal magnetoresistance. Additionally, we present evidence that TaAs2 and NbAs2 are also topologically nontrivial. 3. Graphene is predicted to be a quantum spin Hall insulator, but due to the weak spin-orbit coupling (SOC) of carbon, the predicted bulk energy gap at its Dirac point remains unresolved. Here, we grow ultrathin layers of germanium on Au(1 1 1) in the attempt to realize germanene, a buckled honeycomb structure of germanium atoms, which is predicted to host a similar band structure as graphene with a much larger energy gap. Our ARPES studies of those films reveal the existence of multiple Dirac-like bands that can be tuned by changing the film thickness. 4. The family of A3BO antiperovskites (A=Ca, Sr; B=Sn, Pb) is predicted to form topological crystalline insulators (TCIs). Our ARPES studies of intrinsically hole doped Sr3SnO, Ca3PbO, and Sr3PbO find good agreement with bulk band structure calculations, but cannot probe the predicted bulk and surface Dirac cones in the unoccupied states. For the superconducting hole doped Sr3SnO, which may realize unconventional odd-parity Cooper pairing, we can resolve a controversial question about its Fermi surface morphology that may be relevant for its pairing mechanism.